InfluencetheManagement ofAsepticTechniqueWoundManagement OpenStageII-IIIGenesisAgainstInfection At theGeneral Hospital Daerah Sunan KalijagaDemak - Sarkum Sarkum; Mugi Hartoyo; Tri Arum Utomo (Jurnal LINK, 2013)
Infection is kolonalisasi conducted by foreign species of host organisms, and are Pilang harm the host (Brunner and Suddarth, 2002). Based on preliminary survey Kenanga room Sunan Kalijaga Demak Hospital in January - March 2010 there were 109 patients with open wounds stage I-III due to accidents, there were 9% (9 patients), wound infection characterized by pus out of wounds, sores and dirty looks wet. The purpose of the research was to determine the effect of the management of aseptic techniques in open wound treatment stage II-III on the incidence of infection in Kenanga room Hospitals Sunan Kalijaga Demak. Quasi-experimental research design, methods of correlation. The population of patients open wounds with stage II -III in hospitals Sunan Kalijaga Demak (15 September to 30 October 2010 and 14 - 24 January 2011), the sample is 25 patients. Research tool dalah observation sheet. To determine the influence of the management of aseptic technique in handling the open wound stage II-III on the incidence of infection in Kenanga room hospitals Sunan Kalijaga Demak. Respondents were male sex (88 %), surgery or an open wound for wound surgery hernia respondents (44%) and average treatment time 6 days. Type of clean wounds 24 (96 %) clean contaminated wounds 1 (4 %). Respondents were infected wound 4 (16 %). From the analysis wilcoxon nilai p value 0,048 0,05, so that there is effect the management of aseptic technique in handling the open wound stage II-III on the incidence of infection in Kenanga room hospitals Sunan Kalijaga Demak. The results can be used as a reference in improving and developing methods of prevention and treatment of infection is open sores, especially stage II-III in Kenanga room hospitals Sunan Kalijaga Demak.